KULTUR PENDIDIKAN SAINS PADA PERGURUAN TINGGI ISLAM - Nurhidayat, Muhamad Ramli (LP2M STAI AL-UTSMANI BONDOWOSO, 2025)
This study explores the culture of science education in Islamic higher education institutions, focusing on the integration of modern scientific knowledge with Islamic values. Using a qualitative descriptive approach and library research method, the study analyzes relevant literature to understand how the integration of science and religion is implemented in Islamic academic environments. The findings reveal that science education in Islamic universities emphasizes not only knowledge acquisition but also character development based on Islamic moral and spiritual values. Curriculum design, learning methods, and extracurricular activities play significant roles in creating a holistic academic culture. The synergy between science and religion is essential to nurturing a generation that excels academically while embodying Islamic character and contributing meaningfully to society.